2014
DOI: 10.1155/2014/415160
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure: A Summary of Global Studies and the Need for New Studies from Saudi Arabia

Abstract: Lead poisoning (plumbism) can cause irreversible genetic and reproductive toxicity, hematological effects, neurological damage, and cardiovascular effects. Despite many efforts to minimize lead poisoning, it continues to be a major health concern in many developing and developed countries. Despite efforts to control lead exposure and toxicity, serious cases of lead poisoning increasingly occur as a result of higher vehicular traffic and industrialization. The biomarkers for identification of genetic susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…This transport pathway was thus consistent with the idea that refineries and cement plants may represent anthropogenic sources of Ca. CWT analysis of Pb showed that high observed concentrations in Riyadh aerosol were associated with transport from Iraq, consistent with the continued usage of leaded fuel in that country (Shaik et al, 2014). PM 10 Pb concentrations were 0.035 ± 0.088 µg m −3 in this study, lower than measurements reported for eastern China (0.05 to 0.5 µg m −3 ; Li et al, 2010) and the greater Cairo area (0.3 µg m −3 ; Safar and Labib, 2010), both locations for which leaded fuel has been phased out of usage, and lower than the US ambient concentration standard for lead (0.15 µg m −3 on a 3-month rolling basis; U.S. EPA, 2006).…”
Section: Cwt Analysis For the Ca / Al Ratio Pb Oc And Ecmentioning
confidence: 63%
“…This transport pathway was thus consistent with the idea that refineries and cement plants may represent anthropogenic sources of Ca. CWT analysis of Pb showed that high observed concentrations in Riyadh aerosol were associated with transport from Iraq, consistent with the continued usage of leaded fuel in that country (Shaik et al, 2014). PM 10 Pb concentrations were 0.035 ± 0.088 µg m −3 in this study, lower than measurements reported for eastern China (0.05 to 0.5 µg m −3 ; Li et al, 2010) and the greater Cairo area (0.3 µg m −3 ; Safar and Labib, 2010), both locations for which leaded fuel has been phased out of usage, and lower than the US ambient concentration standard for lead (0.15 µg m −3 on a 3-month rolling basis; U.S. EPA, 2006).…”
Section: Cwt Analysis For the Ca / Al Ratio Pb Oc And Ecmentioning
confidence: 63%
“…This transport pathway is thus consistent with the idea that refineries and cement plants may represent anthropogenic sources of Ca. CWT analysis of Pb shows 390 that high observed concentrations in Riyadh aerosol were associated with transport from Iraq, consistent with the continued usage of leaded fuel in that country (Shaik et al, 2014). were associated with transport from a similar region of the Persian Gulf as was high Pb, the high-concentration source region extended further north, encompassing areas with 402 oil fields and refineries and the Baghdad urban region (Fig.…”
mentioning
confidence: 70%
“…This is consistent with epidemiological studies conducted in Europe, Asia, and America suggesting that the highest genotype of ALAD-2 is found in Caucasian races with ALAD-1/2 proportions of only 18% and ALAD-1 reaching only 1% of the total population. In contrast, in African and Asian racial populations few subjects were found with ALAD-2 genotype [16,22,23]. ALAD polymorphism produces 3 different phenotypes: ALAD-1, ALAD-1/2, and ALAD-2.…”
Section: B Alad Gene Polymorphismmentioning
confidence: 88%